The change of state practice In regards to preemptive self-defense in the presence of nuclear threat: the possibility of preemptive attack by China against North Korea, US invasion of Iraq (2003), Israel bombing Osirak in Iraq (1981) and Israel bombing Al Kibar (2007) - Hamed, Nayera Mohamed (AUC Knowledge Fountain, 2015)
The problem that the project discusses is: state practice in the presence of a nuclear threat challenges self-defense requirement under Article 51 of UN Charter “ the occurrence of an armed attack". In fact, states claim that the imminence of the nuclear threat and necessity of an armed attack regulate their practice in handling it. This is based on Caroline Case principles 1837. The project hypothesis is in the presence of a nuclear threat state practice changes into preemption consistent with Caroline principles. The hypothesis is elaborated in four case studies based on Theory-Guided methodology. The possibility of conducting a preemptive self-defense attack by China against North Korea, United States invasion of Iraq 2003, Israel Bombing Osirak 1981and Israel bombing Al Kibar 2007 are the case studies. The hypothesis states that the four case studies create a new norm of preemption based on Caroline case. The findings do not support the hypothesis. The project interprets that China abides by Article 51 of United Nations, NPT and IAEA regulation in the case of North Korea. Israel and United States practice diverge from International Law and Customary International law requirements of self-defense in the presence of a nuclear weapons threat. In other words, their practices are based on Begin and Bush Doctrines. There is no new norm of preemption consistent with Caroline case in the presence of a nuclear threat.